CHILDREN AND MASS MEDIA - RUZICKA, Evzen (Trends in education, 2010)
The article is focused on children and mass media. It introduces different type of media and wals how they intervene in lives of children and zouny people. It was ascertained in the empiric part through the questionnaire survey whether there is any connection between the child´s age, sex and family background with respekt to the quantity of child´s media usage.
Keywords: Child; mass media; book; periodicals; television; internet.